Safety of bevacizumab and olaparib as frontline maintenance therapy in advanced ovarian cancer: expert review for clinical practice - Romero, Ignacio; Guerra, Eva; Madariaga, Ainhoa; Manso, Luis (Frontiers in Oncology, 2024)
Olaparib, a poly (ADP-ribose) polymerase inhibitor, in combination with the antiangiogenic agent bevacizumab, is approved as maintenance therapy for patients with newly diagnosed stage III or IV epithelial ovarian cancer who have homologous recombination deficient tumors with a deleterious or suspected deleterious BRCA mutation and/or genomic instability, based on the long-lasting survival benefit observed in the PAOLA-1 trial. Despite treatment with olaparib and bevacizumab showed an acceptable safety profile, the rate of discontinuations due to adverse events was relatively high and toxicity related to this regimen may restrict its clinical use. Proper management of olaparib/bevacizumab-related adverse events is important for improvement of quality of life and maximization of efficacy of maintenance therapy. Here, we summarize the safety results of the PAOLA-1 study, focusing on treatment discontinuation reasons and adverse event profile. We sought to shed light on toxicity monitoring and prevention, providing concise recommendations for the clinical management of the most relevant side effects.Genome instability is a hallmark of EOC. In 50% of high-grade serous epithelial carcinoma, the most common histological subtype, there is a homologous recombination deficiency (HRD) due to different mechanisms, with mutations in BRCA1/2 (14.5% germline and 7% somatic mutations) the most prevalent (6). Based on the molecular mechanisms of actions that target key DNA repair Eliminado: